Enhancing Emergency Nurses’ Disaster Nursing Ability and Psychological Resilience: A Randomized Controlled Trial - Lan, Lin; Zhou, Meichi; Wang, Ling; Chen, Xiaoli; Dai, Min; Zhang, Jianna (Emergency Medicine International, 2023)
Objective. This study aimed to investigate emergency nurses’ disaster nursing ability and psychological resilience, validate the effectiveness of a training system for disaster nursing ability based on psychological resilience, and verify the relationship between psychological resilience and disaster nursing ability among emergency nurses. Methods. A training system was developed to enhance psychological resilience and disaster nursing ability. A multicenter, randomized controlled experiment was conducted in five Grade III hospitals in Sichuan Province. A total of 93 emergency nurses were randomly assigned to the following three groups: the blank group, intervention group, and control group. The corresponding interventions were as follows: no intervention, psychological resilience, and nurses’ disaster nursing ability training. Personal information forms, the Connor–Davidson Resiliency Scale, and the Nurses’ Disaster Nursing Ability Assessment Scale were used in the survey. Results. There was no significant difference in the scores of psychological resilience and disaster nursing ability in the blank group in the pretest and posttest (P>0.05). The disaster nursing ability of both the intervention and control groups significantly improved in the posttest (P<0.05). Compared with the control group, the intervention group demonstrated significant improvement in psychological resilience in the posttest (P<0.05). However, there was no statistical difference in psychological resilience scores in the control group in the pretest and posttest (P>0.05). Conclusion. The study concluded that the psychological resilience and disaster nursing ability of emergency nurses could be enhanced through the implemented training system.